Pengembangan Media Pembelajaran Podcast Berbasis Audio dengan Model Addie pada Mata Pelajaran Bahasa Indonesia Kelas VI SDN Deketagung Sugio Lamongan - Ana Purwaningrum; Ibut Priono Leksono; Ujang Rohman (Journal on Education, 2023)
This research was conducted with the aim of: producing learning media products in the form of audio-based Podcasts, adding meaningful variations of technology-based learning media in Indonesian subjects, Updating student learning outcomes using learning media in the form of podcasts. The learning media development model uses the ADDIE development stages, consisting of five stages, namely Analysis (Analysis), Design (Design), Development (Development), Implementation (Implementation) and Evaluation (Evaluation). Data collection instruments used in this development were in the form of questionnaires which were distributed to material experts, learning design experts, media experts, and respondents as well as student achievement. Respondents for the small group and field trials were students of class VI at SDN Deketagung and Elementary Schools in Cluster 04, Sugio Lamongan District. The results of the feasibility test of learning media from material experts got a proportion of 86%, from learning design experts it was 89%, and from media experts it was 94%. The results of the questionnaire data analysis from small group trials the validation results were 88%, from field trials by 90% and student learning outcomes were 90%. Based on the results of this validation, the learning media for Audio-Based Podcasts with the ADDIE Model in Indonesian Class VI Subjects at SDN Deketagung Sugio Lamongan can be interpreted as suitable for use as Indonesian language learning media for class VI.